The use of needle holders in CTF guided biopsies as a dose reduction tool - Sarmento, Sandra; Pereira, Joana S.; Sousa, Maria José; Cunha, Luís T.; Dias, Anabela G.; Pereira, Miguel F.; Oliveira, Augusto D.; Cardoso, João V.; Santos, Luís M.; Santos, João A.M.; Alves, João G. (Journal of applied clinical medical physics, 2018)
Purpose The purpose of this study was to evaluate the efficacy of needle holders in reducing staff hand exposure during biopsies guided by computed tomography fluoroscopy (CTF), through the analysis of data acquired during a detailed monitoring study, undertaken in parallel with an ongoing optimization process to reduce hand irradiation. Methods Hand monitoring was performed with 11 extremity detectors, two per finger (base and tip) and one on the back of the wrist, for the left (dominant) hand, during two series of biopsies with comparable characteristics. The first series (47 biopsies) were performed with only quick‐check method (QC) and occasional side‐handle (SH) manipulation of the needle. The second series (63 biopsies) were performed after introducing needle holders (NH) in the course of an optimization process. Results Choice of technique (QC, QC + NH, QC + SH) by the interventional radiologist (IR) was related to biopsy difficulty. Measured hand exposure was low (< 1 mSv) for all QC‐only procedures, and for most of the QC + NH procedures. Occasional side‐handle manipulation still occurred during challenging biopsies, so that 8% of biopsies in the second series accounted for ~70% of total fingertip dose (~90 mSv). The methodology used allowed a detailed insight into the dose reduction achievable with needle holders during real procedures, without the limitations of phantom measurements. Conclusions Needle holders proved effective in reducing mean hand exposure during clinical procedures where real‐time manipulation was necessary. Occasional side‐handle manipulation was found to contribute disproportionately to hand exposure. This highlights the importance of individual hand monitoring during CTF guided procedures.